The Effect of Brand Image, Brand Trust and Reference Group on the Buying Decision of Sneakers - Miswanto Muslim; Rijal Rizki Mubarok; Nikodemus Hans Setiadi Wijaya (Goodwood Publishing, 2019)
Purpose: This study examines the impact of brand image, brand trust, and reference group on sneaker buying decisions. Understanding these factors is crucial for crafting effective marketing strategies in a competitive market. Research methodology: Primary data were collected through questionnaires from sneaker buyers, selected based on their familiarity with the market. Multiple linear regression was used to analyze the relationship between the independent variables (brand image, brand trust, and reference group) and the dependent variable (buying decision). Results: The hypothesis testing indicated that brand image, brand trust, and reference group all positively affect sneaker buying decisions. Consumers are more likely to purchase sneakers from brands they trust and have a positive perception of, and those influenced by their reference groups. These findings suggest that brand reputation and social influence play a significant role in purchasing decisions. Conclusion: The study found that brand image, brand trust, and reference group positively influence buying decisions for sneakers. Consumers tend to choose brands they trust, perceive positively, and are influenced by their social circle. Future research could explore other factors, such as price and personal preferences, to further understand consumer behavior in the sneaker market. Limitations: This study only considered three factors, while other variables such as price and personal taste may also influence buying decisions. Contributions: This research provides valuable insights for marketers, contributing to the understanding of factors influencing sneaker buying decisions and offering a foundation for future studies in sneaker marketing.